Sistem Pendukung Keputusan Penentuan Insentif Kinerja Dosen Dengan Menggunakan Metode Saw - cantika; Yuza Reswan; Agung Kharisma Hidayah; A.R Walad Mahfuzi (Jurnal Sistem Informasi dan E-Bisnis, 2024)
In the context of higher education, the role of faculty members holds a significant impact on the quality of national education and the image of educational institutions. Faculty members play a crucial role in realizing comprehensive education, including the development of faith/taqwa, noble character, knowledge, technology, arts, and an advanced and cultured society. The performance of faculty members influences areas such as accreditation and teaching quality. The importance of faculty members' role in education makes additional appreciation in the form of incentives reasonable and effective in enhancing their performance. Performance-based incentives can encourage an increase in faculty productivity in carrying out their core duties, namely teaching, research, and community service. In this context, faculty members tend to focus more on teaching than on research and community service. Managing the allocation of incentives for faculty members is the responsibility of the campus or university. To streamline and expedite the process of determining appropriate incentives, the author intends to develop an application using the Simple Additive Weight (SAW) method. This method can calculate the weight of predefined criteria to provide recommendations for incentive amounts based on variables such as teaching, research, and community service. Consequently, this application has the potential to offer a more efficient solution for managing incentives for faculty members. The criteria data provided include publications, teaching, research, and community service. The application can display calculation results in the form of an incentive data table consisting of faculty names, scores, statuses, and incentive amounts